Comparing ALADIN-CZ and ALADIN-LAEF Precipitation Forecasts for Hydrological Modelling in the Czech Republic. (18th September 2018) - Vokoun, Martin; Hanel, Martin
Abstract : Precipitation forecasting has great significance for hydrological modelling, particularly for issuing flood alerts. This study assesses the high-resolution deterministic model ALADIN-CZ (Aire Limitée, Adaptation Dynamique, Development International–Czech Republic) and the ensemble model ALADIN-LAEF (Limited Area Ensemble Forecasting). Verified precipitation data were modified to the form in which they enter the hydrological model used for flood forecasting in the Czech Republic. ALADIN-LAEF, unlike ALADIN-CZ, is currently not considered to be of any value for hydrological predictions in the Czech Republic. In the present paper, we assess the added value of the ensemble model. The most significant rainfall events from the summer seasons during 2011–2015 were selected for the purpose of this study. The results show that ALADIN-LAEF does not have a lower success rate than ALADIN-CZ in predicting significant rainfall events. In fact, for the most verification scores and metrics, ALADIN-LAEF was assessed as more skilful. Surprisingly, the high-resolution ALADIN-CZ does not yield higher success rates than ALADIN-LAEF even at short prediction lead times. This is due to spatial aggregation into hydrological regions, with an area significantly larger than the resolution of the forecasting models. Furthermore, the relationship between synoptic weather types, hydrological regions, and predictability was considered. It was found that the worst prediction results are related to weather situation C (cyclone over central Europe), which dominantly affects Berounka and Lower Elbe catchments.